Analisis Pengaruh Sukuk dan Sukuk Berkelanjutan terhadap Reputasi Perusahaan - Shinta Riani; Yurniwati Yurniwati; Vima Tista Putriana (Universitas Batanghari Jambi, 2022)
This study aims to analyze the effect of sukuk and sustainable sukuk on the company's reputation. The population of this study are publicly listed companies on the Indonesia Stock Exchange. The research sample was carried out by sampling using purposive sampling technique, with observations for 3 years. Hypothesis testing in this study using multiple regression analysis and different tests. The results show that sukuk have no effect on the company's reputation, while sustainable sukuk have an effect on the company's reputation. There is no difference between the reputation of the sukuk issuing company and the reputation of the sustainable sukuk issuing company. The results of the analysis of the coefficient of determination show that sustainable sukuk affect the company's reputation by 11.2%.